2014
DOI: 10.1364/ao.53.005367
|View full text |Cite
|
Sign up to set email alerts
|

Percolation threshold determination of sputtered silver films using Stokes parameters and in situ conductance measurements

Abstract: This work presents a straightforward approach to determine the percolation threshold of silver thin films deposited by magnetron sputtering on various oxide layers at room temperature. The proposed method is based on the observation of the coupling of p-polarized light with local surface plasmons. By measuring the first Stokes parameter in real time, one can determine the moment at which the nano-islands of silver begin to coalesce into a continuous film. We confirm the results by in situ and ex situ conductan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…4(a). Starting with samples fabricated as described above, we then deposited a second Ag film, 5 nm thick to be below the percolation threshold of ~6 nm 44 , on top of the random nanopattern that results from the aforementioned annealing process. Optical characterization, as shown by the purple curve in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4(a). Starting with samples fabricated as described above, we then deposited a second Ag film, 5 nm thick to be below the percolation threshold of ~6 nm 44 , on top of the random nanopattern that results from the aforementioned annealing process. Optical characterization, as shown by the purple curve in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Surface morphology of ultrathin metal lms is particularly important for their electrical and optical properties, as it was already shown that discontinuous formations such as islands, grains, or perforations might have a detrimental effect on transparency and resistance. [31][32][33][34] Deposition of nucleation layer has been recognized as an effective approach to improve the homogeneity of the metal lm. Metal oxides or ultrathin metal layer is typically introduced to assure continuous layer growth, although other techniques, e.g.…”
Section: Mam Multilayer Optimizationmentioning
confidence: 99%
“…We studied the influence of the morphology of the molecular layer on the plasmon resonance excitation mechanisms and their polarization properties in assemblies using Fourier-Transform Infrared Spectroscopy (FTIR), UV-vis near-infrared spectroscopy, and modulation-polarization spectroscopy (modulation polarimetry) [40,41].…”
Section: Introductionmentioning
confidence: 99%